Evolving Waqf Reporting Practices: Towards Comprehensive Integrated Reporting and Stakeholder Engagement - Yuvitasari, Gusranti; Ihsan, Hidayatul; Dwiharyadi, Anda (Universitas Negeri Padang, 2026)
Accountability in waqf management is commonly demonstrated through financial reporting by nazhir to waqf stakeholders. While financial reporting plays a central role in ensuring accountability, it is often insufficient to capture the broader dimensions of waqf management, particularly in explaining performance outcomes, achievement of objectives, and social impacts. Moreover, differences in stakeholders’ levels of accounting literacy may create information gaps, limiting the effectiveness of financial reports as a communication tool. As a result, non-financial reporting is increasingly recognized as a necessary complement to financial reporting. This study aims to explore integrated reporting practices, encompassing both financial and non-financial dimensions, in relation to the sustainability of waqf entities. Stakeholder salience theory is employed as an analytical framework to examine how reporting practices respond to the information needs of different stakeholder groups. Adopting a qualitative and exploratory approach within an interpretive paradigm, data were collected through in-depth interviews and document analysis, and analyzed using thematic network analysis. he findings indicate that waqf institutions have begun to incorporate elements of integrated reporting by combining financial disclosures with non-financial information related to program activities and social impacts. However, these practices remain fragmented, as non-financial reporting components are not standardized and vary across waqf entities. This study contributes to the literature on waqf accountability and reporting by highlighting the emerging but incomplete nature of integrated reporting practices in the waqf context. Practically, the findings offer insights for nazhir and regulators in strengthening reporting practices to enhance transparency, accountability, and stakeholder understanding of waqf performance and impact.